Weight-based enoxaparin thromboprophylaxis in young trauma patients: analysis of the CLOTT-1 registry - Sarah Lombardo; Ram Nirula; Elliott R Haut; Scott Brakenridge; Brandon Bruns; Charles E Wade; M Margaret Knudson; Thomas Scalea; Todd W Costantini; Lisa Marie Knowlton; David Spain; Ernest E Moore; et al. (Trauma Surgery & Acute Care Open)
Introduction Optimal venous thromboembolism (VTE) enoxaparin prophylaxis dosing remains elusive. Weight-based (WB) dosing safely increases anti-factor Xa levels without the need for routine monitoring but it is unclear if it leads to lower VTE risk. We hypothesized that WB dosing would decrease VTE risk compared with standard fixed dosing (SFD).Methods Patients from the prospective, observational CLOTT-1 registry receiving prophylactic enoxaparin (n=5539) were categorized as WB (0.45–0.55 mg/kg two times per day) or SFD (30 mg two times per day, 40 mg once a day). Multivariate logistic regression was used to generate a predicted probability of VTE for WB and SFD patients.Results Of 4360 patients analyzed, 1065 (24.4%) were WB and 3295 (75.6%) were SFD. WB patients were younger, female, more severely injured, and underwent major operation or major venous repair at a higher rate than individuals in the SFD group. Obesity was more common among the SFD group. Unadjusted VTE rates were comparable (WB 3.1% vs. SFD 3.9%; p=0.221). Early prophylaxis was associated with lower VTE rate (1.4% vs. 5.0%; p=0.001) and deep vein thrombosis (0.9% vs. 4.4%; p<0.001), but not pulmonary embolism (0.7% vs. 1.4%; p=0.259). After adjustment, VTE incidence did not differ by dosing strategy (adjusted OR (aOR) 0.75, 95% CI 0.38 to 1.48); however, early administration was associated with a significant reduction in VTE (aOR 0.47, 95% CI 0.30 to 0.74).Conclusion In young trauma patients, WB prophylaxis is not associated with reduced VTE rate when compared with SFD. The timing of the initiation of chemoprophylaxis may be more important than the dosing strategy. Further studies need to evaluate these findings across a wider age and comorbidity spectrum.Level of evidence Level IV, therapeutic/care management.